Industry of the future. Issue 11 (November 2017) - Won, Rachel
Giorgio Anania, the vice president of Photonics21 and CEO of Aledia,  a French developer of GaN microwire LEDs, discusses the impact of the Photonics Public Private Partnership on jobs and growth in Europe and the importance of investing in future industries.